Strategy for Enhancing Catalytic Active Site: Introduction of 1D material InSeI for Electrochemical CO2 Reduction to Formate - Jeon, Jiho; Bang, Hyeon Seok; Ko, Young Jin; Kang, Jinsu; Zhang, Xiaojie; Oh, Cheoulwoo; Kim, Hyunchul; Choi, Kyung Hwan; Woo, Chaeheon; Dong, Xue; Lee, Woong Hee; Yu, Hak Ki; et al. (Small Methods, 2024)
The presence of oxygen vacancies (Vo) in electrocatalysts plays a significant role in improving the selectivity and activity of CO2 reduction reaction (CO2RR). In this study, 1D material with large surface area is utilized to enable uniform Vo formation on the catalyst. 1D structured indium selenoiodide (InSeI) is synthesized and used as an electrocatalyst for the conversion of CO2 to formate. The electrochemical treatment of InSeI leads to the leaching of Se and I from the catalyst surface and the formation of Vo. The resulting Vo promotes the activity of the CO2RR, which increases the local pH of the catalyst surface and chemically maintains the oxidized metal sites on the catalyst. Owing to these characteristics, activated In wire exhibited remarkable CO2RR activity, thereby surpassing 93% FEformate at 500 mA cm−2, with a maximum of 97.3% FEformate at 100 mA cm−2. Moreover, the catalytic activity remained consistent for over 50 h at 100 mA cm−2 (FEformate >88%). Thus, the findings imply that using 1D materials can facilitate the formation of oxygen vacancies on the catalyst surface and improve the selectivity and durability of CO2RR. This indicates the potential for further research on 1D materials as electrocatalysts.
Keywords: 1D materials; Catalyst surfaces; Catalytic active sites; CO 2 reduction; CO2 reduction reaction; Electrochemicals; Formate; Indium selenoiodide wire; Reduction reaction; ]+ catalyst; 1D materials; CO2 reduction reaction (CO2RR); electrocatalysts; formate; InSeI wire